Efficiency and Safety of Pulmonary Rehabilitation in Acute Exacerbation of Chronic Obstructive Pulmonary Disease - He, Mei (Med Sci Monit, 2015)
BACKGROUND: Pulmonary rehabilitation (PR) is able to improve dyspnea, endurance capacity, and health-related quality of life in chronic obstructive pulmonary disease (COPD) patients, but it is rarely used in China. This study aimed to assess the effectiveness and safety of PR after exacerbation of COPD. MATERIAL/METHODS: Patients admitted to hospital due to an exacerbation of COPD were randomized to receive either PR or routine care (control group). The PR program was performed from the second day of admission until discharge. The pre-post changes in 6-minute walk distance (6MWD), self-reported quality of life (QOL) assessed by CAT score and CRQ-SAS score, and activity of daily life assessed by ADL-D score were determined. The perceived end-effort dyspnea (Borg scale) was measured throughout the study. RESULTS: A total of 101 patients were enrolled, of whom 7 withdrew after randomization, and 94 completed this study. There were 66 patients in the PR group and 28 in the control group. The 6MWD, resting SpO(2), and exercise Borg dyspnea score were significantly improved in the PR group. In addition, the PR group had greater improvement in the total CRQ-SAS score and had a lower CAT score. Significant improvements were also found in the ADL-D and BODE index in the PR group. No adverse events were recorded during exercise. CONCLUSIONS: Our study provides evidence that it is safe and feasible to apply an early PR in patients with acute exacerbation of COPD.